Arsenic Contamination at District Deoria (Uttar Pradesh), India - Mishra, Jwala Prasad; Kumar, Ankit (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 7 No 1 (2020): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
In the present time arsenic contamination in ground water and its affect to human life have been one of the serious problems of world. The contamination of drinking water supplies with natural occurring arsenic is major health problem. In the present chapter, authors have studied the arsenic contamination at district Deoria (Uttar Pradesh), India. The complete study is divided in three regions of arsenic namely Region-I (safe region of the arsenic), Region-II (low risk region of arsenic) and Region-III (high risk region of arsenic). For this, authors selected seven study sites of district Deoria with two types of samples from shallow water and deep (India mark II) water. Results are presented in the tabular form and show that at five study sites (Bankata, Barhaj, Bhaluani, Rudrapur and Salempur) of district Deoria (Uttar Pradesh), India, concentration of arsenic both in the shallow as well as in the deep bore well water samples is found in high risk region (Region-III) while at the remaining two study sites (Bhatpar Rani and Tarkulwa) of district Deoria (Uttar Pradesh), India, concentration of arsenic both in the shallow as well as in the deep bore well water samples was found in low risk region (Region-II). Results also depict that the ground water of Bankata, Barhaj, Bhaluani, Bhatpar Rani, Rudrapur, Salempur and Tarkulwa is not fit for drinking without processing. How to cite this article: Mishra JP, Kumar A. Arsenic Contamination at District Deoria (Uttar Pradesh), India. J Adv Res Alt Energ Env Eco 2020; 7(1): 33-36. DOI: https://doi.org/10.24321/2455.3093.202010